2012 IEEE International Conference on Management of Innovation &Amp; Technology (ICMIT) 2012
DOI: 10.1109/icmit.2012.6225843
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cultural dimension on MIS acceptance

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
1
1
Order By: Relevance
“…Even though the relationship was not significant, it was in the expected direction (β = 0.169). Previous studies had shown a positive direction between CD and PU of technological innovations (Sriwindono & Yahya, 2012). Thus, we concluded that CD has a positive effect on a user's PU of RPA, albeit the strength is not strong.The relationship between CB and PU was positive but not significant (β = 0.053, p > 0.05).…”
Section: Discussioncontrasting
confidence: 47%
“…Even though the relationship was not significant, it was in the expected direction (β = 0.169). Previous studies had shown a positive direction between CD and PU of technological innovations (Sriwindono & Yahya, 2012). Thus, we concluded that CD has a positive effect on a user's PU of RPA, albeit the strength is not strong.The relationship between CB and PU was positive but not significant (β = 0.053, p > 0.05).…”
Section: Discussioncontrasting
confidence: 47%
“…It is evident that the usage of appropriate ICT can be an effective tool in supporting the teaching and learning process (Langrova & Poulova, 2013;Ott & Pozzi, 2011;Sriwindono & Yahya, 2012). ICT has transformed the conventional way of our education systems.…”
Section: Impacts Of Ict Usementioning
confidence: 99%